Tata Ruang Rumah Tradisional Desa Pengotan - Pandu Sukma Demokrat; I Nyoman Suarsana; Ni Made Wiasti (Department of Anthropology Udayana University, 2019)
The form and function of the spatial structure of the traditional village of Pengotan are fully integrated with the life of the Pengotan Village community. Because the traditional house of Pengotan Village plays a very important role in various matters relating to community activities, especially the issue of sacred activities. These activities form a strong bond to the form and function of the traditional village of Pengotan. The traditional village of Pengotan strongly applies the upstream-teben concept to its location, shape and layout. Oriented to the north because it focuses worship on the Mount Batur region. The traditional village of Pengotan is built in a row between one house and another and is called the shadow puppet theater. The most purified building area is the northernmost and the most profane is the southernmost. There are three zones in a traditional house, namely: the upstream zone, the middle zone, and the teben zone. In the upstream zone there is a Sanggah building. the middle zone is the uma meten and bale adat building separated by natah. Then there are angkul-angkul in the teben zone. The form and function of the traditional village of Pengotan are integrated with the life of the people of Pengotan Village. Seen from the main function that is used for activities that smell sacred like traditional ceremonies. Especially large traditional ceremonies such as mass wedding and mass cremation. Behind the manifest function or function that is realized by the community there is a latent function that is not or has not been realized by the community. The latent function of the traditional village of Pengotan if observed is that of a scale and noetic energy pool so as to form a strong bond. The bond creates a harmony that is very supportive of daily community activities in Pengotan Village.